2021
DOI: 10.1002/er.6616
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐input and single‐output voltage control for a polymer electrolyte fuel cell system using model predictive control method

Abstract: Efficient and robust control strategies can greatly contribute to the reliability of fuel cell systems, and a stable output voltage is a key criterion for evaluating a fuel cell system's reliability as a power source. In this study, a polymer electrolyte fuel cell (PEFC) system model is developed, and its performances under different operating conditions are studied. Then two different novel controllers-a proportional integral derivative (PID) controller and a model predictive control (MPC) controller-are prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…The reason for undertaking this approach is that an exact model accounting for all the complex subsystems involved in an FCS is impractical for robust stability analysis and control design. 5,7,36 This simplification enables a solution to the aforementioned problems, but using a simple and realizable controller, as we demonstrate.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The reason for undertaking this approach is that an exact model accounting for all the complex subsystems involved in an FCS is impractical for robust stability analysis and control design. 5,7,36 This simplification enables a solution to the aforementioned problems, but using a simple and realizable controller, as we demonstrate.…”
Section: Introductionmentioning
confidence: 89%
“…To facilitate the analysis, we refrain from using intricate models and instead analyze an uncertain system, which portraits the unknown variable nature of the load and fuel cell stack. The reason for undertaking this approach is that an exact model accounting for all the complex subsystems involved in an FCS is impractical for robust stability analysis and control design 5,7,36 . This simplification enables a solution to the aforementioned problems, but using a simple and realizable controller, as we demonstrate.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The feedback and feed‐forward control using the PID controller have been applied to obtain better fuel cell performance [9, 10]. However, it has been found that this method has certain drawbacks, such as a limited control range and insufficient constraint capacity, and the tuning method “trial and error” is adopted to find suitable coefficients [11]. As a result, inconsistent control effects may arise when it is applied under varying operating conditions.…”
Section: Introductionmentioning
confidence: 99%